Personagens públicas na mídia, persongens públicas em nós: experiências contemporâneas nas trajetórias de Gisele Bündchen e Luciana Gimenez - Ligia Campos de Cerqueira Lana (2012)
This thesis investigates the concept of public character having as example the trajectories of Gisele Bündchen and Luciana Gimenez. Initially, the idea of public character is explained in contrast with related concepts, such as: idols, stars, celebrities and people. The study argues that the public character is constituted through me in straight connection to we. The public character aims to be recognized by ordinary people who then make the valuation of its attributes, giving him (or not) the fame. The case study about the trajectories of Gisele Bündchen and Luciana Gimenez analyses texts of Brazilian popular media. Three moments are taken: the emergence of both, between 1998 and 2000, the wedding ceremonies of each one, respectively, in 2009 and 2006 and the motherhood, recently happened in 2009 to 2011. The texts are seen as narratives of events, looking for the main context where it occurs. The challenges of womens speech and the power of media in contemporary life are also analyzed on the case study. In conclusion, the specifics of each trajectory indicates that not only attributes that are appropriate to media could give someone fame. The recognition of public character is related to broader elements of the experience. Although with specific trajectories each, Gisele Bundchen and Luciana Gimenez act similar when its about keeping the public recognition